Kontribusi Dinasti Abbasiyah Bidang Ilmu Pengetahuan - Salmah Intan (Rihlah : Jurnal Sejarah dan Kebudayaan, 2018)
This article aimed to reveal the progress of Muslims in the fields  of religion, philosophy, education and science in the era Abbasid Dynasty, they were: the history of the emergence of the Abbasids, and the progress achieved by the Abbasids in the fields of religion, philosophy, education and science.The Abbasid dynasty was officially established in 750 AD, founded by Abu Abbas al-Saffah who was assisted by Abu Muslim al-Khurasani by seizing the power from the previous dynasty (Banu Umayah). During the Abbasid dynasty, developments and advances in various fields were fairly rapid. At that time, Muslims had reached the peak of glory, both in the fields of economics, civilization and power. In addition, various branches of science have also developed, coupled with the many translations of books from foreign languages to Arabic. In the field of religious science, several scholars emerged in the field of law or fiqh with various schools. The field of hadith found efforted to trace and collect hadith andthe science of interpretation hadalso stood alone. In the field of science and technology, medical science or medicine had developed quite rapidly, which was marked by the establishment of medical schools which also established institutions in certain fields such as Bait al-Hikmah. Tulisan ini bertujuan mengungkapkan tentang kemajuan umat Islam dalam bidang ilmu agama, filsafat, pendidikan dan sains pada masa Dinasti Abbasiyah. Dinasti Abbasiyah secara resmi berdiri pada tahun 750 M., didirikan oleh Abu Abbas al-Saffah yang dibantu oleh Abu Muslim al-Khurasani dengan merebut kekuasaan dari dinasti sebelumnya (Bani Umayah). Pada masa itu, Umat Islam telah mencapai puncak kemuliaan, baik dalam bidang ekonomi, peradaban dan kekuasaan. Selain itu juga telah berkembang berbagai cabang ilmu pengetahuan, ditambah lagi dengan banyaknya penerjemahan buku-buku dari bahasa asing ke bahasa Arab. Dalam bidang ilmu agama, muncullah beberapa ulama dalam bidang hukum atau fikih dengan berbagai mazhab. Dalam bidang hadis ditemukan usaha-usaha untuk penelusuran dan penghimpunan hadis. Ilmu tafsir yang sudah berdiri sendiri. ilmu kedokteran atau pengobatan telah berkembang cukup pesat, yang ditandai dengan berdirinya sekolah kedokteran juga dibangun lembaga dalam bidang tertentu seperti Bait al-Hikmah.